Big data and its impact on digitized supply chain management - Tahiduzzaman, Md.; Rahman, Mustafizur; Dey, Samrat Kumar; Rahman, Md. Sumon; Akash, S. M. (IJRDO - Journal of Business Management, 2017)
Day by day the customers demand changing rapidly, it is very difficult for a company to identify demand. Big data used in supply chain management helps to create better customer demand planning strategies by collecting, documenting & analyzing data in a real situation. Big data combined a set of data usually referred as large and complex datasets; enables the company to review real-time data flows. Digitized supply chains have the potential to dramatically lower costs, reduce lead time and increase product availability. Digitization makes the supply chain more effective, agile and responsive by sharing knowledge and collaborating complex supplier networks. As a result, this research work helps a manager to identify the current situation of their business and it will help them to take timely, fast and better decision.